Economy as Religion: The Case of China - Strijdom, Johan ca. 21. Jh. (Religion & theology, 2024)
Engaging David Chidester’s argument that takes up ideas from Marx and Benjamin, the article argues that the academic study of religion can make a contribution to understand the economy by conceptualising it as functioning like a religion. This is achieved by using theorised concepts of myth (sacred stories), rituals and institutions that serve not only to unite adherents, but also to establish, maintain or challenge power relations. The thesis is tentatively illustrated with reference to the Chinese economy that needs to be compared with other economic systems that function like a religion.